Plasma Astrophysics, Part I Fundamentals and Practice - Somov, Boris V.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This two-part book is devoted to classic fundamentals and current practices and perspectives of modern plasma astrophysics. This first part uniquely covers all the basic principles and practical tools required for understanding and work in plasma astrophysics. More than 25% of the text is updated from the first edition, including new figures, equations and entire sections on topics such as magnetic reconnection and the Grad-Shafranov equation. The book is aimed at professional researchers in astrophysics, but it will also be useful to graduate students in space sciences, geophysics, applied physics and mathematics, especially those seeking a unified view of plasma physics and fluid mechanics.
From the Contents: Plasma Astrophysics: History and Neighbours -- Particles and Fields: Exact Self-Consistent Description -- Statistical Description of Interacting Particle Systems -- Weakly-Coupled Systems with Binary Collisions -- Propagation of Fast Particles in Plasma -- Motion of a Charged Particle in Given Fields -- Adiabatic Invariants in Astrophysical Plasma -- Wave-Particle Interaction in Astrophysical Plasma -- Coulomb Collisions in Astrophysical Plasma.
Keywords: Space sciences; Plasma (Ionized gases).; Geophysics; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Plasma Physics; Geophysics and Environmental Physics